2016
DOI: 10.1080/00016489.2016.1195013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cartilage graft and fascia in type 1 tympanoplasty: systematic review and meta-analysis

Abstract: Eight eligible articles with 915 patients were reviewed. The pooled OR for graft take rate was 3.11 (95% CI =1.94-5.00; p = 0.43) and the difference between the two groups was significant, which means that the cartilage grafts group got a better graft take rate than the temporalis fascia grafts group. The pooled MD for mean AIR-BONE-GAP gain was 1.92 (95% CI = -0.12-3.95; p < 0.000 01) and the difference was not significant. However, in the full thickness cartilage grafts sub-group, the pooled MD for mean AIR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…While this systematic review specifically excluded studies that reported results of palisade cartilage tympanoplasty combined with other procedures, an overall graft take rate of >97% has been reported in patients with who underwent combined palisade tympanoplasty with mastoidectomy for pathologies such as as cholesteatoma, adhesive otitis, and chronic mucosal disease [13, 18]. Our results are consistent with previous systematic reviews that demonstrate superior graft integration rate with cartilage tympanoplasty compared to temporalis fascia [8, 19]. Those studies did not examine palisade cartilage tympanoplasty alone by subgroup analysis, and thus, our systematic review and meta-analysis offers specific outcomes regarding the clinical effectiveness of this technique, the cartilage palisade tympanoplasty.…”
Section: Discussionsupporting
confidence: 88%
“…While this systematic review specifically excluded studies that reported results of palisade cartilage tympanoplasty combined with other procedures, an overall graft take rate of >97% has been reported in patients with who underwent combined palisade tympanoplasty with mastoidectomy for pathologies such as as cholesteatoma, adhesive otitis, and chronic mucosal disease [13, 18]. Our results are consistent with previous systematic reviews that demonstrate superior graft integration rate with cartilage tympanoplasty compared to temporalis fascia [8, 19]. Those studies did not examine palisade cartilage tympanoplasty alone by subgroup analysis, and thus, our systematic review and meta-analysis offers specific outcomes regarding the clinical effectiveness of this technique, the cartilage palisade tympanoplasty.…”
Section: Discussionsupporting
confidence: 88%
“…12,13 Similarly, in this study group A cases (which was subjected to underlay periosteal graft) had better hearing results with mean difference of -11 dB ± 5 SD compared to group B cases, where inlay cartilage grafting was used which had a mean difference of -9 dB ± 7 SD with statistically significant P value of 0.01. However, Yang et al, 14 in 2016, concluded in a meta-analysis retrospective study that 1 year follow up of patients underwent full thickness type I cartilage tympanoplasty had better hearing than others underwent tympanoplasty using temporalis fascia. Yang's study conclusion gave the rise to question about the long term hearing results of cartilage tympanoplasty which seems to be better on the long run.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum follow‐up duration of the included studies for hearing improvement was 3 months. Recently, Yang et al published the results of a meta‐analysis in type 1 tympanoplasty. They included only the retrospective studies with duration of follow‐up more than 12 months comparing cartilage grafting with TF.…”
Section: Introductionmentioning
confidence: 99%